Análise das Políticas Governamentais definidas para a Região do Rio Madeira e seus efeitos sobre a pesca artesanal - (:unkn) unknown (Universidade Federal do Amazonas, 2009)
The object of this thesis is to examine government policies and projects that are now being implemented along the Madeira River and extend from the border with Bolivia, passing through the State of Rondônia, to the Amazon. This is an analysis of the plans, projects, and government programs defined for this region, considering their effects on artisanal fishing practices between Humaitá - AM and Porto Velho - RO. I examine the social changes occurring in this region and the social struggles of resistance to these policies, waged by social workers in these municipalities.
Keywords: Pesca; Política; Rio Madeira; Movimentos Sociais; Fishing; Politics; Rio Madeira; Social Movements; CIÊNCIAS HUMANAS: SOCIOLOGIA